Tinjauan Yuridis Mengenai Sengketa Kepemilikan Hak Atas Tanah Antara TNI dan Warga Sipil di Indonesia - Deslin, Mayang Fitria Putri (UNES Law Review, 2023)
Land disputes are conflicts that occur between individuals or groups who have the same relationship or interest in an object of ownership of land rights which give rise to legal consequences for one another. One form of land dispute that occurs between individuals/groups and government institutions is between the Indonesian National Army (TNI) and civilians in Indonesia. Land disputes between the TNI and civilians occurred because there was no proof of ownership or certificate for the disputed land. The TNI is a government institution under the Ministry of Defense, therefore the right to land used for the TNI's interests is the right to use as regulated in Article 41 of the Basic Agrarian Law (UUPA). The land obtained came from state land, land controlled by the Dutch army, historical control by the Japanese army and land obtained by purchasing, acquiring, procuring, revoking and relinquishing land rights. Settlement of land disputes between civilians and the TNI can be carried out through legal channels for resolving land disputes which includes several stages including the preparation stage, the dispute handling and resolution stage and the litigation stage in court.